Analyzing the Formation of Nanobubbles and its Effect on the Stability of Dissolved Oxygen in Water - Fitriani, Mita; Nugroho, Fairuz Gianirfan; Rochman, Nurul Taufiqu; Ansari, Abu Saad (Faculty of Advanced Technology and Multidiscipline Universitas Airlangga, 2025)
Nanobubbles (NB) have attracted many researchers due to their unique characteristics, one of which is increasing the amount of dissolved oxygen (DO) in liquids, making them a promising technology for various applications, such as water treatment and aquaculture. This study investigates the generation of NBs using a custom-designed cartridge nozzle and evaluates their effectiveness in sustaining elevated DO concentrations. Experiments were carried out under a controlled gas pressure of 400 N/m2 comprising a 30-minute active phase with the generator turned on, followed by a 30-minute passive phase with the generator off, to assess NB formation and stability. The results showed that smaller nanobubbles had higher stability, allowing dissolved oxygen to stay longer in the water. Particle size analysis revealed the production of uniformly distributed NBs averaging approximately 600 nm, which remained structurally stable even after gas input ceased. During the active phase, DO levels increased sharply, peaking at 28.51 mg/L by the 10th minute. Although a gradual decline was observed after pressurization stopped, DO levels remained significantly higher than baseline, indicating the prolonged oxygen retention capability of NBs. This performance is attributed to the slow dissolution kinetics, high zeta potential, and favorable interfacial interactions of the bubbles. Overall, the cartridge nozzle-based method demonstrates strong potential for applications in water treatment, aquaculture, and other processes requiring efficient and sustained oxygen delivery.